The method of moments in electromagnetics - Gibson, Walton C. (Chapman & Hall/CRC, 2015)
This book discusses the use of integral equations in electromagnetics, covering theory only when necessary to explain how to apply it to solve practical problems. To introduce the method of moments, coupled surface integral equations are derived and solved in several domains of pragmatic concern: two-dimensional problems, thin wires, bodies of revolution, and generalized three-dimensional problems. Focusing on real-world implementation, the Second Edition includes a treatment of electromagnetic scattering from objects that may be either conducting or comprise a composite conducting/dielectric (material) geometry